2003
DOI: 10.1080/312703002119
|View full text |Cite
|
Sign up to set email alerts
|

T He Prehospital Administration of Intravenous Methylprednisolone Lowers Hospital Admission Rates for Moderate to Severe Asthma

Abstract: Patients with moderate to severe asthma who receive intravenous methylprednisolone in the prehospital setting have significantly fewer hospital admissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…In an attempt to explore whether the effect of systemic steroids extended to the prehospital arena, Knapp et al published a retrospective case review comparing admission rates in patients with moderate to severe asthma exacerbations who received 125 mg IV methylprednisolone via EMS compared to in the ED. 26 They found that patients who received steroids via EMS had a lower admission rate (13% compared to 33%) and had a quicker resolution of symptoms (15 +/− 7 minutes compared to 40 +/− 22 minutes).…”
Section: Resultsmentioning
confidence: 99%
“…In an attempt to explore whether the effect of systemic steroids extended to the prehospital arena, Knapp et al published a retrospective case review comparing admission rates in patients with moderate to severe asthma exacerbations who received 125 mg IV methylprednisolone via EMS compared to in the ED. 26 They found that patients who received steroids via EMS had a lower admission rate (13% compared to 33%) and had a quicker resolution of symptoms (15 +/− 7 minutes compared to 40 +/− 22 minutes).…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that the study quality of one 19 is poor and the inferences are probably hypothesis generating at best. The second, 20 whilst better in quality, provides weak evidence of an effect. Randomised controlled trials and subsequent meta-analysis does however provide strong evidence of benefit, at least in an ED setting.…”
Section: Discussionmentioning
confidence: 95%
“…Of these four articles, only two were comparative studies. [19][20] These two comparative studies were critically appraised by two reviewers (DL, JB). This low number was not unexpected due to the dearth of out-of-hospital research.…”
Section: Out-of-hospital Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…62,63 Preliminary evidence now suggests a decreased odds of admission for the moderate-to-severe asthmatic patient who receives very early prehospital (vs. in-hospital) corticosteroid administration. 64 After extensive discussion, however, the group concluded the evidence for prehospital steroids to be of insufficient strength to include this treatment in the model. Therefore, the critical therapy of choice, by either EMT-basics or paramedics, remains the beta-agonist intervention.…”
Section: Bronchospasmmentioning
confidence: 97%